Prediksi Harga Cabai Rawit di Provinsi Jawa Timur Menggunakan Metode Fuzzy Time Series Model Lee - Komaria, Vida; Maidah, Nova El; Furqon, Muhammad Ariful (Computer Engineering Departement, Universitas Komputer Indonesia, 2023)
ABSTRACT - East Java is the province with the most significant amount of chili pepper production in Indonesia based on data from BPS in 2021 which is around 41.75. Chili pepper is a commodity that high price fluctuations that will impact several parties, so a mechanism is needed to predict the price of chili pepper to become a consideration in decision making. Lee's fuzzy time series method can be used to predict time series stationary or non-stationary data. The research was conducted using historical data on the price of red and green chili peppers in East Java Province from April 2017 to February 2023 with a weekly data period of 307 data. The Z1 and Z2 values used to get the smallest error results are Z1 = 950 and Z2=400 for red chili peppers while for green chili peppers values the Z1 and Z2=100. The error value of forecasting red chili pepper prices is MAE = 4,469.04 RMSE = 6,138.64 MAPE = 13.09% (good MAPE value category) and the error value for green chili pepper is MAE = 1,486.15 RMSE = 2,211.06 and MAPE = 6.72% (very good MAPE value category). Keywords – forecasting; Lee’s fuzzy time series; chili pepper price; MAPE; Python